Correlation between crystallographic anisotropy and dendritic orientation selection of binary magnesium alloys. Issue 1 (December 2017) - Du, Jinglian; Guo, Zhipeng; Zhang, Ang; Yang, Manhong; Li, Mei; Xiong, Shoumei
Abstract Both synchrotron X-ray tomography and EBSD characterization revealed that the preferred growth directions of magnesium alloy dendrite change as the type and amount of solute elements. Such growth behavior was further investigated by evaluating the orientation-dependent surface energy and the subsequent crystallographic anisotropyvia ab-initio calculations based on density functional theory andhcp lattice structure. It was found that for most binary magnesium alloys, the preferred growth direction of the α-Mg dendrite in the basal plane is always $$\langle 11\bar{2}0\rangle $$ 〈 11 2 ¯ 0 〉, and independent on either the type or concentration of the additional elements. In non-basal planes, however, the preferred growth direction is highly dependent on the solute concentration. In particular, for Mg-Al alloys, this direction changes from $$\langle 11\bar{2}3\rangle $$ 〈 11 2 ¯ 3 〉 to $$\langle 22\bar{4}5\rangle $$ 〈 22 4 ¯ 5 〉 as the Al-concentration increased, and for Mg-Zn alloys, this direction changes from $$\langle 11\bar{2}3\rangle $$ 〈 11 2 ¯ 3 〉 to $$\langle 22\bar{4}5\rangle $$ 〈 22 4 ¯ 5 〉 or $$\langle 11\bar{2}2\rangle $$ 〈 11 2 ¯ 2 〉 as the Zn-content varied. Our results provide a better understanding on the dendritic orientation selection and morphology transition of magnesium alloys at the atomic level.